Konsep Diri Dan Liyan (Other) Dalam Pandangan Filsafat Dakwah - Musarofah, Siti (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2024)
In general, the aim of preaching is to change human behavior both individually and socially. In order to achieve this goal, a preacher needs to understand the concept of self and others. This research aims to understand the concept of self and other from the perspective of da'wah philosophy, as well as knowing the implications of understanding the concept of self and other from the perspective of missionary philosophy. Literature review was used in writing this article. This research produced the following findings: (1) self-concept is understood as an individual's perspective on themselves, both physically, intellectually, emotionally, spiritually and socially. So others are people who are separated, marginalized, from the roles of managing shared life because they are considered not included in a particular social community (2) Understanding the concept of self and other in preaching is important because it can have implications for: increasing the effectiveness of preaching, strengthening good relations between preachers and the object of da'wah, as well as between fellow preachers, strengthening the internalization of da'wah values, and the success of social change efforts.